Child Support for Juvenile Inmates from an Islamic Legal Perspective: A Case Study of Tanjung Gusta Correctional Facility - Widya Kusvie Ayuningtyas; Muhibbussabry (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2024)
This research aims to investigate the role of parents in meeting their children’s basic needs, especially when children lack parental care, guidance, and affection. This study uses empirical legal research methodology from a sociological perspective. Apart from that, the author used an analytical and descriptive research approach in conducting this research. Sources were also obtained from interviews conducted directly with children who experienced a lack of satisfaction with their living resources, perhaps due to the living conditions that were not in Tanjung Gusta Prison. Secondary data refers to information obtained by searching for and collecting items relevant to the research subject, such as journals, papers, books, and the Internet. The findings of this research determine that parental involvement in raising children is very important, especially in shaping the child’s internal well-being. This applies even when the child is an orphan and also takes into account the maqasid syariah perspective on the treatment of children. Children experience expenses related to school and basic needs during the learning process. Therefore, parents are responsible for providing financial support to their children. According to Law No. 23 of 2002, a child is defined as an individual under 18 years of age, including newborn babies